TRAINING, MOTIVATION, LEADERSHIP, AND COMPETENCY EFFECTS ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Saputra, Oktaria; Hidayatulloh, Furqon Syarief; Ekananta, Arry (International Journal of Social Service and Research, 2024)
The purpose of this study is to investigate the influence of training, motivation, leadership, and competence on employee performance with job satisfaction as a mediating variable at the Deputy I of the Ministry of Youth and Sports of the Republic of Indonesia. The research contributes to understanding how factors such as training, motivation, leadership, and competence influence employee performance with job satisfaction as a mediating variable at the Deputy I of the Ministry of Youth and Sports of the Republic of Indonesia. The study population included all 131 employees under Deputy II, comprising civil servants, PPPK, and institutional honorary staff. The data were collected through questionnaires structured with a modified Likert scale. Structural Equation Modeling (SEM) using Partial Least Square (PLS) and SPSS was applied to simultaneously examine both structural relationships between latent variables and measurement relationships between indicators. The results of this study succeeded in proving that leadership has a positive and significant effect on employee job satisfaction. Second, leadership is a good leader. Fourth, competence affects job satisfaction, the results show that good competence cannot always produce high employee performance. The findings can inform strategies for enhancing employee development and satisfaction, ultimately improving performance outcomes within governmental institutions.